Some De0terminants of Behaviour in Power Situations - Dixit, Narendra (My University, 1979)
The main objective of the present study was to investigate sex and cultural differences in the use of power and the way power is affected by personality-traits as well as by expectation about the other person. This investigation was carried out in two parts. The first part utilized a questionnaire and in the second part three laboratory experiments were conducted.
In the first part of the study a 3 x 2 matrix was used which gave the subjects the opportunity to give the other person more than, equal to or less than what they could have for themselves or to take for themselves more than, equal to or less than what they could give to the other person. Canadians, especially Canadian males, were found to give the other person more than what they could have for themselves and also to take more for themselves than what they could give to the other person as compared with Canadian females and Indians of both sexes.
In the second part of the study three experiments using a modified Prisoner's Dilemma Game were carried out which involved Canadian Ss (both males and females) only. In the first experiment, Ss denied those in a high power position more than those in a low power position. Females were also more "denying" than males. The second experiment investigated the effect of power reversal under conditions of 'Information' and 'No Information' about the switch. Ss denied more in the 'Information' than in the 'No Information' Condition' and 'Information' resulted in more 'denying' responses in the Ss before the switch whereas in 'No Information' Ss 'denying' responses increased considerably after the switch in power positions. The effects of machiavellianism and empathic tendency on the use of power were not found to be very great but the expectations about the other person's behaviour did affect responding for those in both the high power or low power positions.
Keywords: Social Psychology; Social Psychology